Oligomerization of Cry9Aa in solution without receptor binding, is not related with insecticidal activity - Longfa Fang; Bo Wang; Zishan Zhou; Sujuan Yang; Changlong Shu; Fuping Song; Alejandra Bravo; Mario Soberón; Jie Zhang (Electronic Journal of Biotechnology, 2016)
Background: Bacillus thuringiensis Cry toxins bind with different insect midgut proteins leading to toxin oligomerization, membrane insertion and pore formation. However, different Cry toxins had been shown to readily form high molecular weight oligomers or aggregates in solution in the absence of receptor interaction. The role of Cry oligomers formed in solution remains uncertain. The Cry9A proteins show high toxicity against different Lepidoptera, and no-cross resistance with Cry1A. Results: Cry9Aa655 protein formed oligomers easily in solution mediated by disulfide bonds, according to SDS-PAGE analysis under non-reducing and reducing conditions. However, oligomerization is not observed if Cry9Aa655 is activated with trypsin, suggesting that cysteine residues, C14 and C16, located in the N-terminal end that is processed during activation participate in this oligomerization. To determine the role of these residues on oligomerization and in toxicity single and double alanine substitution were constructed. In contrast to single C14A and C16A mutants, the double C14A–C16A mutant did not form oligomers in solution. Toxicity assays against Plutella xylostella showed that the C14A–C16A mutant had a similar insecticidal activity as the Cry9Aa655 protein indicating the oligomers of Cry9Aa formed in solution in the absence of receptor binding are not related with toxicity. Conclusions: The aggregation of Cry9Aa655 polypeptides was mediated by disulfide bonds. Cry9Aa655 C14 and C16C are involved in oligomerization in solution. These aggregate forms are not related to the mode of action of Cry9Aa leading to toxicity.